ENVIRONMENTALISTS-AFL-CIO CHALLENGE FOOD EXEMPTION: GMA INTERVENES TO AID STATE - NEDELMAN J (Tufts Archival Research Center, 2007)
Memo describing a suit filed against the Governor of California. Says that the GMA asked to intervene on behalf of the governor. Claims that included with the memo are the press kits from the parties involved. Outlines a litigation strategy to deal with the suit.